Magnetophonon Resonance in Quantum Wells with Parabolic Potential - Hoi, Bui Dinh; Lam, Vo Thanh; Phong, Tran Cong (Communications in Physics, 2012)
The linear dc magnetoconductivity in the (x,y) plane of a parabolic quantum well, with a magnetic field B = Be_z applied, is evaluated for electron - optical phonon interaction. For nonpolar optical and polar optical phonons, the magneto-conductivity oscillates as a function of the magnetic field with resonances occurring when Pω_c=ω_0, where ω_c and ω_0 are cyclotron frequency and optical phonon frequency, respectively, and where P is an integer. The analytic results are numerically evaluated to show explicitly the dependence of magneto-conductivity on the magnetic field, the confinement frequency in z direction, and the temperature of the system.